Protein C deficiency as the major cause of thrombophilias in childhood. Issue 3 (18th June 2013) - Ohga, Shouichi; Ishiguro, Akira; Takahashi, Yukihiro; Shima, Midori; Taki, Masashi; Kaneko, Masatoki; Fukushima, Kotaro; Kang, Dongchon; Hara, Toshiro; ,
Abstract Genetic predisposition of thromboembolism depends on the racial background. Factor V Leiden (G1691A) and factor II mutation (G20210A) are the leading causes of inherited thrombophilias in Caucasians, but are not found in Asian ancestries. Protein S (PS), protein C (PC) and antithrombin (AT) activity are reportedly low in 65% of adult Japanese patients with deep vein thrombosis. Approximately half of the patients with each deficiency carry the heterozygous mutation of PS (PROS1; 20%), PC (PROC; 10%), and AT genes (SERPINC1: 5%). Recently, several studies have revealed an outline of inherited thrombophilias in Japanese children. Congenital thrombophilias in 48 patients less than age 20 years consisted of 45% PC deficiency, 15% PS deficiency and 10% AT deficiency, along with other causes. All PS‐ and AT‐deficient patients had a heterozygous mutation of the respective gene. On the other hand, PC‐deficient patients were considered to carry the homozygous or compound heterozygous mutation in 50%, the heterozygous mutation in 25%, and unknown causes in the remaining 25% of patients. Half of unrelated patients with homozygous or compound heterozygous PROC mutations carried PC‐nagoya (1362delG), while their parents with its heterozygous mutation were asymptomatic. Most of the PC‐deficient patients developed intracranial lesion and/or purpura fulminans within 2 weeks after birth. Non‐inherited PC deficiency also conveyed thromboembolic events in early infancy. The molecular epidemiology of thrombosis in Asian children would provide a clue to establish the early intervention and optimal anticoagulant therapy in pediatric PC deficiency.